Determinan Manajemen Laba Yang Dipengaruhi oleh Mekanisme Good Corporate Governance Pada Perusahaan Subsektor Transportasi Periode 2017-2019 - Rina Putri Leksono; Hari Setiono; Muhammad Bahril Ilmiddaviq (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2022)
Transportation sector plays an important role in improving Indonesia's economy. But there is company transportation in Indonesia do earnings management. Implementing good corporate governance would be very helpful in minimize it. This purpose’s study to determine the effect of GCG proxied by board of directors, independent commissioners, institutional ownership and foreign ownership of earnings management using discretionary accruals. The population is transportation subsector companies listed on IDX period 2017-2019. Samples amounted 15 companies obtained with purposive sampling technique. Quantitative research methods used with descriptive analysis, multiple regression, classical assumption and hypothesis test as data analysis. Results of this study, board of directors (0.799), independent commissioners (0.507) and foreign ownership (0.321) partially have no effect on earnings management (>0.05) while institutional ownership has significant effect on earnings management (0.025<0.05). Simultaneously all of these variables have no effect on earnings management (0.184>0.05). Company is expected to be more optimal in implementing GCG and closely monitor management so it can minimize earnings management.